Upper Echelon Employment: A Review of the Fundamental Questions Related to the Executive Labor Market - Withers, Michael C.; Lee, Kyung Hwan; Bermiss, Y. Sekou; Boivie, Steven (Journal of Management, 2024)
The executive labor market (ELM) is a topic of interest that spans several academic fields. The outcomes of the ELM, including executive selection, succession, and compensation, are important considerations as they influence executive decision making and other organizational outcomes. Yet, a comprehensive framework of ELM dynamics currently does not exist. To address this shortcoming, we reviewed the existing literature using five fundamental questions: (1) What executive jobs are available? (2) Who is available to fill executive jobs, and what is valued on the ELM? (3) Who signals interest in the executive jobs? (4) Who gets offered/accepts the executive job, and what is the agreed-upon compensation? (5) How do status and social capital influence ELM outcomes? By answering these questions, our review provides a framework for integrating existing research on the ELM while suggesting avenues for future research.